O Voo Do Macuco Criação Cultural, História E Memória Na Região Cacaueira (1976-1997) - Rusciolelli, Alexandre Magno [UNIFESP] (2018)
In The Dissertation I Sought To Document The Trajetory Of The Macuco (Gam), Founded In The City Of Buerarema, South Of Bahia In 1976, And Had Until 1990 A Predomint Role In The Artistic Cultural Scenario In This City And In The Cacao Region: The Promoted The Buerarema Arte Fairs, Which For Several Years Were Cinstituted As A Referencefor Various Artists And Grouo In The City And Region To Present Their Works; Have Also Played A Significant Role In The Regional Theater Since The Assembl And Sataging Of Several Shows, Among Which Are Worth Mentioning Green Cacao Or Not Everything That Glitters Is Gold, Macuco Arte Group An Indsutr Of Dreams, The Marriage Completed Of Catumbira With Sinháfulô, Cometery Of The Invisible And God And The In Brzilian Land. They Also Revealed Several Actors Such As Joseph Delmo Ramon Vane, Jackson Costa, Carlos Alberto, Alba Cordelia And Gal Macuco. In A First Of This Work I Tried To Situate Historicall In A Certain Space-Time-Memory, The Municipality Of Buerarema, Constructed From D